Fe3O4 nanopearl decorated carbon nanotubes stemming from carbon onions with self-cleaning and microwave absorption properties1. Issue 67 (24th July 2015) - Lu, Xianyong; Wu, Yanzi; Cai, Hongyan; Qu, Xingyuan; Ni, Lingmei; Teng, Chao; Zhu, Ying; Jiang, Lei
<x xml:space="preserve">Abstract</x> A water shedding carbon onion/carbon nanotube@Fe3O4 nanocomposite film prepared using a flame strategy possesses self-cleaning and microwave absorption properties.